2017
DOI: 10.12783/dtetr/ictim2016/5493
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rutting Resistance of Asphalt Pavements with Different Asphalt Mixtures

Abstract: ABSTRACT:The main objective of this study was to compare the rutting resistance of asphalt pavements with different asphalt mixtures used in the middle and bottom asphalt layers. The uniaxial compression test, uniaxial repeated load creep test and the rutting depth simulation were conducted. The results showed that the modified asphalt pavement structure (SBS and PR composite modified AC-20 mixture was used in the middle asphalt layer and BRA modified Superpave-25 mixture was used in the bottom asphalt layer) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…By comparing the performance differences of materials before and after oil erosion using conventional testing methods, they assess the oil erosion resistance. Cao et al [4] evaluated the impact of oil erosion on the performance of asphalt mixtures using the laboratory IDT test. Chen et al [5] analyzed the impact of oil erosion on the high-temperature performance of asphalt mixtures, and found that oil erosion significantly reduced the Marshall stability and dynamic stability, with diesel oil having a greater impact than engine oil.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the performance differences of materials before and after oil erosion using conventional testing methods, they assess the oil erosion resistance. Cao et al [4] evaluated the impact of oil erosion on the performance of asphalt mixtures using the laboratory IDT test. Chen et al [5] analyzed the impact of oil erosion on the high-temperature performance of asphalt mixtures, and found that oil erosion significantly reduced the Marshall stability and dynamic stability, with diesel oil having a greater impact than engine oil.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have conducted research to enhance the anti-fuel erosion abilities of asphalt pavements. The design of a dense asphalt pavement with small porosity can effectively reduce fuel erosion damage [6]. Furthermore, the sealants and anti-fuel erosion agents have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement in the anti-fuel erosion performance of SBS-modified asphalt generated by Sasobit is evaluated via the fuel immersion test. The dynamic shear rheometer (DSR) test is carried out on the asphalt after fuel immersion to At present, the assessment methods of the anti-fuel erosion of asphalt mixtures are mainly based on the Marshall stability (MS) test [4,5], splitting tensile strength test [4,6], rutting test [7] and freeze-thaw splitting test [8]. Moreover, the mass loss ratio of asphalt mixtures after fuel immersion can quickly and intuitively evaluate the anti-fuel erosion performances of asphalt mixtures, and it is widely used [9][10][11].…”
Section: Introductionmentioning
confidence: 99%